Lacrimal tissue resection in Fasanella Servat operation and the correlation to dry eye. (3rd May 2020) - Golan, Shani; Vingopoulos, Filippos; Olson, Luke C.; Patel, Hency H.; Pinchover, Shulamit; Magro, Cynthia M.; Levine, Benjamin; Lelli, Gary J.
ABSTRACT: Purpose : Fasanella-Servat operation (FSO) was previously reported to be associated with post-operative dry eyes due to accessory lacrimal gland resection during the surgery. We performed a retrospective, cohort study to determine the frequency of lacrimal tissue resection during FSO and its correlation with post-operative eye dryness and keratopathy. Methods : Review of all patients who underwent FSO at New York-Presbyterian Weill Cornell Hospital over a two-year period (2013–2015). Patients were included only if they had adequate histopathological specimens of the resected tissue obtained during surgery. Outcomes included the study of the pathological specimen for the presence of lacrimal tissue; Post-operative dry eye symptoms and pre- and post-operative corneal epitheliopathy. Results : 46 patients with a total of 58 eyelid resections were studied. Eight eyelids (13.7%) were found to have lacrimal tissue present in the pathology specimens. Postoperatively, nine patients reported some symptoms of dry eye and new-onset keratopathy was noted in four eyes (6.8%), only one of which had lacrimal tissue present in histopathology specimen obtained from surgery. Discussion : Previous studies found lacrimal tissue present in up to 43% of specimens resected during FSO. Our data found a lower rate of lacrimal tissue resection during FSO, and did not find an association between lacrimal tissue resection and post-operative dryness or epitheliopathy. Conclusion : Our study is one of few to examine histopathological resections from the FSO. We found that lacrimal tissue is not frequently resected during FSO, and when it is resected, there is no increased incidence of post-operative dryness or keratopathy.